Analisis Komparatif Tentang Corak Ajaran Tarekat Tijaniah - Maulani (HUMANISTIKA : Jurnal Keislaman, 2023)
This research aims to trace the network of the Tijaniah congregation in Indonesia, especially in West Java and to explain the similarities and differences in the teachings of the Tijaniah congregation which were developed at the Zawiyah Garut Islamic boarding school and the Cirebon Buntet Islamic boarding school. This research is categorized as field research using qualitative methods, and data collection uses direct observation techniques and in-depth interviews, and data analysis is carried out in a descriptive-comparative way. This study found that the Tijaniah congregation at the Zawiyah Garut Islamic Boarding School and the Cirebon Buntet Islamic Boarding School both practice the wirid ladzimah, wadzifah, and hailalalh, in which the three wirid contain istighfar or requests for forgiveness, blessings, and remembrance of Allah SWT. In addition, the authors also found differences in the style of teaching between the Zawiyah Garut Islamic boarding school and the Cirebon Buntet Islamic boarding school. The teachings of the Tijaniah congregation at the Zawiyah Islamic Boarding School in Garut have an Islamic-fundamental pattern, and the teachings of the Tijaniah congregation at the Buntet Islamic Boarding School, Cirebon, have a moderate-Islamic pattern.